Structure determination from lipidic cubic phase embedded microcrystals by MicroED - Zhu, Lan (Structure, 2020)
The lipidic cubic phase (LCP) technique has proved to facilitate the growth of high-quality crystals that are otherwise difficult to grow by other methods. However, crystal size optimization process could be time- and resource-consuming, if it ever happens. Therefore, improved techniques for structure determination using these small crystals is an important strategy in diffraction technology development. Microcrystal electron diffraction (MicroED) is a technique that uses a cryo-TEM to collect electron diffraction data and determine high-resolution structures from very thin micro- and nanocrystals. In this work, we have used modified LCP and MicroED protocols to analyze crystals embedded in LCP converted by 2-Methyl-2,4-pentanediol (MPD) or lipase, including proteinase K crystals grown in solution, cholesterol crystals and human adenosine A(2A) receptor crystals grown in LCP. These results set the stage for the use of MicroED to analyze microcrystalline samples grown in LCP, especially for those highly challenging membrane protein targets.